1997
DOI: 10.1136/hrt.78.4.382
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atrial septal defect morphology by transthoracic three dimensional echocardiography using standard grey scale and Doppler myocardial imaging techniques: comparison with magnetic resonance imaging and intraoperative findings

Abstract: Objective-To determine whether transthoracic three dimensional echocardiography is an accurate non-invasive technique for defining the morphology of atrial septal defects (ASD). Methods-In 34 patients with secundum ASD, mean (SD) age 20 (17) years (14 male, 20 female), the measurements obtained from three dimensional echocardiography were compared to those obtained from magnetic resonance imaging (MRI) or surgery. Three dimensional images were constructed to simulate the ASD view as seen by a surgeon. Measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
(15 reference statements)
1
24
0
1
Order By: Relevance
“…It gives a stretched diameter but our study clearly showed a very poor correlation between the stretched diameter and the threedimensional echocardiography maximal diameter, particularly in atrial septal defects of complex shapes: balloon measurement overestimates the size of round defects by stretching the septum tissue and underestimates the size of multiple defects by measuring only one hole. Furthermore, two-dimensional transoesophageal echocardiography is currently used to assess the (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) 2DE=rim surrounding the atrial septal defect obtained by two-dimensional transoesophageal echocardiography; 3DE=measurements obtained by three-dimensional echocardiography; Mean diff=mean difference between the two methods; AS=antero-superior rim; PS=postero-superior rim; AI=antero-inferior rim; PI=postero-inferior rim.…”
Section: Patient Selection For Device Closurementioning
confidence: 99%
See 1 more Smart Citation
“…It gives a stretched diameter but our study clearly showed a very poor correlation between the stretched diameter and the threedimensional echocardiography maximal diameter, particularly in atrial septal defects of complex shapes: balloon measurement overestimates the size of round defects by stretching the septum tissue and underestimates the size of multiple defects by measuring only one hole. Furthermore, two-dimensional transoesophageal echocardiography is currently used to assess the (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) 2DE=rim surrounding the atrial septal defect obtained by two-dimensional transoesophageal echocardiography; 3DE=measurements obtained by three-dimensional echocardiography; Mean diff=mean difference between the two methods; AS=antero-superior rim; PS=postero-superior rim; AI=antero-inferior rim; PI=postero-inferior rim.…”
Section: Patient Selection For Device Closurementioning
confidence: 99%
“…Three-dimensional echocardiography provides unique 'en face' views of intracardiac structures such as the mitral valve and the atrial septum [8][9][10][11] . Previous studies have shown the feasability of three-dimensional echocardiography reconstructions of atrial septal defects [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 3D provides unique views of the interatrial septum and allows en-face views of the ASD. These views clearly define the morphology of the defect, as it has been shown to change during the cardiac cycle, 15 and its relation to contiguous cardiac structures thereby providing details which cannot be attained as easily by any other imaging technique ( Figure 2 major implications in the selection of patients for device closure. The use of 2D biplane imaging, a feature of commercially available 3D imaging transducers and software, is a complementary and sometimes sufficient option to the use of 3D imaging ( Figure 3).…”
mentioning
confidence: 99%
“…Gerade die Einschätzung des Randsaums ist jedoch für die Auswahl des Devices und die generelle Entscheidung zum Device-Verschluss von großer Bedeutung. Die 3-D-Echokardiographie konnte somit diagnostische Lücken, die häufig nach konventioneller echokardiographischer Beurteilung verbleiben, schließen (Abbildungen 7a bis 7d) [36,37]. Darüber hinaus ist die Methode geeignet, das Ergebnis nach erfolgter Implantation eines Verschlusssystems zu kontrollieren.…”
Section: Angeborene Herzfehlerunclassified